Retrocaval Ureter A Case Report (Journal of Dhaka Medical College, 2015)
Retrocaval ureter is a rare congenital urologic anomaly. It occurs due to the persistence of the right subcardinal veins during embryologic development. Its presence should be suspected with the finding of a characteristic S-shaped deformity on intravenous or retrograde pyelography. Today, a definitive diagnosis can be made noninvasively using multi-slice CT imaging or MRI. Intervention is indicated in the presence of functionally significant obstruction leading to pain or renal function deterioration.J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 259-261